2017
DOI: 10.18632/oncotarget.17344
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of leptin receptor in human glioblastoma: Correlation with vasculogenic mimicry and poor prognosis

Abstract: Vasculogenic mimicry (VM) was an important tumor blood supply to complement the endothelial cell-dependent angiogenesis, while leptin and receptor (ObR) involved in angiogenesis in glioblastoma has been reported on previous study, but the relationship between ObR expression and VM formation in human glioblastoma tissues, as well as their prognostic significance still remains unclear. In our study, we found that VM recognized by CD31-/PAS+ immunohistochemical staining in glioblastoma tissues showed a positive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…Significant expression of the leptin receptor has been shown in CD133+ cells and knockdown of leptin receptor effectively lowered the invasiveness of stem-like cells in gliomas and confirmed that JAK/STAT3 signaling is the molecular mechanism involved in the invasion of U87 glioma cells (Han et al, 2013). Another study suggests ObR as an important target for anti-cancer therapy as the ObR+ glioblastoma cells possessing glioblastoma stem cell properties were associated with vasculogenic mimicry formation and microvascular density (MVD) (Han et al, 2017). Extensive research has been carried out in mammary tumors with respect to these antibodies.…”
Section: Discussionmentioning
confidence: 88%
“…Significant expression of the leptin receptor has been shown in CD133+ cells and knockdown of leptin receptor effectively lowered the invasiveness of stem-like cells in gliomas and confirmed that JAK/STAT3 signaling is the molecular mechanism involved in the invasion of U87 glioma cells (Han et al, 2013). Another study suggests ObR as an important target for anti-cancer therapy as the ObR+ glioblastoma cells possessing glioblastoma stem cell properties were associated with vasculogenic mimicry formation and microvascular density (MVD) (Han et al, 2017). Extensive research has been carried out in mammary tumors with respect to these antibodies.…”
Section: Discussionmentioning
confidence: 88%
“…Leptin receptor also displayed prognostic power in clinical. Patients of glioblastoma revealed poor prognosis as high leptin receptor levels were detected [ 15 ]. The association of leptin receptor with poor recurrence-free survival ( P =0.09) and cancer-specific survival ( P =0.01) by log-rank test was observed, and data from Cox regression analysis further characterized leptin receptor as an independent predictor of poor survival respectively with P =0.011 and 0.006 in upper tract urothelial carcinomas [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 92% of the colorectal carcinoma cases with pronounced leptin receptor expression, high rate of angiogenesis case was observed alone with the correlation of low grade neoangiogenesis and leptin receptor absence (88.2% of the cases) [ 8 ]. In addition, the correlation of leptin receptor with vasculogenic mimicry (VM) formation had been reported in glioblastoma [ 15 ]. Moreover, HIF-1α RNA and protein expression of leptin and leptin receptor were high in tissue samples of oral squamous cell carcinoma which indicated the potential crosslink in regulating angiogenesis [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…VM is a non-endothelium-dependent vasculature to complement the endothelium-dependent vessels in providing oxygen and nutrients for malignant tumor cells. Although it has been widely investigated in the pathology of glioma which is characterized by increased microvasculature in tumor tissues [26,27], the molecular mechanism governing VM formation in glioma remains largely unknown. Our previous study has shown that Cav-1 and HIF-1α play important roles in the progress of glioma, and both of them are significantly associated with glioma prognosis [35].…”
Section: Discussionmentioning
confidence: 99%